Adaptive Nonlinear Equalization for Digital Array Receivers - Peccarelli, Nicholas L.; Fulton, Caleb (IEEE transactions on microwave theory and techniques, 2019)
As low-cost fully digital array technology becomes more commercialized, techniques need to be developed to be able to deal with many of the inherent problems of these systems. This article focuses on mitigating the intermodulation distortion (IMD) caused by the low-input third-order intercept point (IIP3) of the low-noise amplifier (LNA) in a digital array element's channel. The performance of solid-state electronics also varies with the temperature of the device, thus changing the device's nonlinear characteristics. This article proposes an adaptive solution for nonlinear equalization (NLEQ) with the use of the least mean-square (LMS) algorithm. Data from a modern digital array channel are corrected using the proposed method; the channel nonlinearities are also characterized for further simulations. A simulation using these nonlinear coefficients shows that NLEQ can effectively mitigate the IMD of two strong interferers that had previously distorted the weak signal of interest. Finally, a nine-element fully digital array is simulated, showing the correlation of IMD with specific, predictable directions, and the decorrelation of these spurs after NLEQ is applied to each element of the array.